1997
DOI: 10.1152/jappl.1997.82.3.760
|View full text |Cite
|
Sign up to set email alerts
|

Both physical fitness and acute exercise regulate nitric oxide formation in healthy humans

Abstract: We analyzed nitrate, a major stable end product of nitric oxide (NO) metabolism in vivo in plasma and urine from groups of healthy subjects with different working capacities. Resting plasma nitrate was higher in athletic subjects than in nonathletic controls [45 +/- 2 vs. 34 +/- 2 (SE) microM; P < 0.01]. In other subjects, both the resting plasma nitrate level (r = 0.53; P < 0.01) and the urinary excretion of nitrate at rest (r = 0.46; P < 0.01) correlated to the subjects' peak work rates, as determined by bic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
120
6
4

Year Published

2000
2000
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(148 citation statements)
references
References 23 publications
16
120
6
4
Order By: Relevance
“…51 In another study conducted by Jungersten, it was determined that the plasma NO 3 levels of the athletes were significantly greater than the sedentary, and also that there was a positive correlation between VO 2 max and basal NOx levels. 19,52 Result of studies indicated that, even though there was no significant difference in terms of basal NO levels between sedentary and exercise groups, there was a significant relationship between aerobic capacities and blood NO levels. These findings may indicate the presence of a vasodilator and metabolic regulator potential that forms through training and can be triggered with exercise, which may have a role of NO in these results.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…51 In another study conducted by Jungersten, it was determined that the plasma NO 3 levels of the athletes were significantly greater than the sedentary, and also that there was a positive correlation between VO 2 max and basal NOx levels. 19,52 Result of studies indicated that, even though there was no significant difference in terms of basal NO levels between sedentary and exercise groups, there was a significant relationship between aerobic capacities and blood NO levels. These findings may indicate the presence of a vasodilator and metabolic regulator potential that forms through training and can be triggered with exercise, which may have a role of NO in these results.…”
Section: Discussionmentioning
confidence: 98%
“…18 In addition, it has been found that there is a significant relationship between aerobic fitness level and NO. 17,19 Therefore, increasing NO levels may have a positive effect on physiological stress and OS levels during OWS. NO is synthesized from L-arginine, which is catalyzed by nitric oxide synthase (NOS).…”
mentioning
confidence: 99%
“…6,33 On exercise treadmill test with modified Bruce protocol, NO concentration also increased to 110.7 AE 58.5 μmol/L (range, 61.0-348.8 μmol/L), but there were no differences of baseline NO concentration before and after exercise treadmill test in all 31 patients (p ¼ 0.157).…”
Section: F2-isoprostane and No Production In Patients Hospitalized Wimentioning
confidence: 90%
“…This positive relation may help to explain the beneficial effects of physical exercise on cardiovascular health. 6 The basal release of endothelium-derived NO is increased with 4 weeks of home based training in hypercholesterolemic patients, independently of lipid profile modification. This may contribute to the cardiovascular protective effects of exercise training, including reduced blood pressure, which may show that exercise conveys benefit beyond lipid profile modification via elevation in basal NO production.…”
Section: ö öZ Ze Et T Amentioning
confidence: 97%
“…7 It was found that only moderate-intensity aerobic exercise augments endothelium-dependent vasodilation through the increased production of nitric oxide, but not mild or high and that high-intensity exercise possibly increases oxidative stress. 8 In another study, it has been shown that long term different training strategies establish different basal nitrites and lipid peroxidation Turkiye Klinikleri J Med Sci 2012;32 (6) Özkol ve ark.…”
Section: ö öZ Ze Et T Amentioning
confidence: 99%